Analisis Customer Retention Dalam Ritel Online Data United States E-Commerce Records 2020 - Andy Hermawan; Muhamad Fauzi Hakim; B Hilda Nida Alistiqlal; Bagas Dio Hanggoro (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study investigates the level of customer loyalty in e-commerce in the United States in 2020. Using e-commerce customer data from 2020 available on Kaggle, this research analyzes cohort retention to understand the number of customers from each cohort who continue to make purchases in subsequent months. Additionally, this study evaluates the implementation of data analysis to assess the effectiveness of promotional strategies and their impact on customer loyalty and retention. The results show that retention percentages decline over time, with the number of active customers decreasing after registration. However, some cohorts exhibit better retention performance. For instance, the April cohort saw a significant increase from 18.46% to 29.23%, and the May cohort experienced the highest increase from 14.29% to 30.16%. On the other hand, the January cohort showed the most drastic retention drop from 100% to 10.42% after the first month, with the largest monthly decline from 23.96% in April to 7.29% in May. These findings provide practical guidance for e-commerce companies in developing more effective strategies to improve customer retention. Further analysis is recommended to understand the specific causes of these retention trends and to develop more holistic strategies to support better business decisions and increase long-term profitability.